2020
DOI: 10.1101/2020.02.10.942615
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Arid1aloss potentiates pancreatic β-cell regeneration through activation of EGF signaling

Abstract: The dynamic regulation of β-cell abundance is poorly understood. Since chromatin remodeling plays critical roles in liver regeneration, these mechanisms could be generally important for regeneration in other tissues. Here we show that the ARID1A mammalian SWI/SNF complex subunit is a critical regulator of β-cell regeneration. Arid1a is highly expressed in quiescent β-cells but is physiologically suppressed when β-cells proliferate during pregnancy or after pancreas resection. Whole-body Arid1a knockout mice we… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 78 publications
0
1
0
Order By: Relevance
“…Our previous study found that vitamin D switches the binding partner of vitamin D receptor (VDR) from the BRD9containing SWI/SNF complex to the BRD7 containing PBAF complex, resulting in increased chromatin accessibility at VDR targets and enhancing the anti-inflammatory and anti-stress responses in b-cells (44). Another recent study showed that deletion of ARID1A-containing BAF complex in b cells promotes b regeneration under an STZ challenge (45). Therefore, the various compositions of the SWI/SNF complex defines the diverse molecular and biological function of chromatin remodeling complexes in b cells.…”
Section: The Major Classes Of Epigenetic Modification and Their Roles In Regulating B Cell Dysfunction Chromatin Modifications And Accessmentioning
confidence: 99%
“…Our previous study found that vitamin D switches the binding partner of vitamin D receptor (VDR) from the BRD9containing SWI/SNF complex to the BRD7 containing PBAF complex, resulting in increased chromatin accessibility at VDR targets and enhancing the anti-inflammatory and anti-stress responses in b-cells (44). Another recent study showed that deletion of ARID1A-containing BAF complex in b cells promotes b regeneration under an STZ challenge (45). Therefore, the various compositions of the SWI/SNF complex defines the diverse molecular and biological function of chromatin remodeling complexes in b cells.…”
Section: The Major Classes Of Epigenetic Modification and Their Roles In Regulating B Cell Dysfunction Chromatin Modifications And Accessmentioning
confidence: 99%